Hopeless Activism: Performance in the Anthropocene*. Issue 4 (1st October 2016) - Haas, Benjamin
ABSTRACT: This essay carves out the ethical responsibilities and an identity position for the hopeless activist in the Anthropocene. The author concludes that ethical witnessing is the first step toward an embracing of the power of hopelessness of continued human survival on planet earth. Calling upon temporally posthuman theory and Derridean thought about death the author posits human extinction as an embraceable and inevitable feature of modern life. Once human extinction is taken as a given, the responsibility toward other species becomes a more necessary ethical commitment. Finally the essay calls on performance scholars to lead this charge.